Rancangan Strategi Eceran dalam Upaya Meningkatkan Partisipasi Anggota Pelanggan Koperasi Konsumen Mulia RSUD Majalaya - Lely Savitri Dewi; Fadillah Nur Huda; Muhammad Haris Fadhillah (J-Coop : Journal of Co-operative, 2025)
Mulia Consumer Cooperative of Majalaya Regional General Hospital has 584 members; in terms of participation, only 56% of the total cooperative members participate. This shows that member participation is not optimal, whereas in essence, in the development of cooperatives, members as customers must participate in the form of purchasing products for cooperative trading units. In this context, retail strategy analysis plays a role in determining how to achieve competitive advantage, expand market share, and meet member needs. This research was conducted to find out the level of member participation, the strategies applied in the Cooperative Trading Unit, as well as the condition of the Cooperative's strengths, weaknesses, opportunities, and threats through the IFAS and EFAS matrix and the SWOT matrix. The research method used in this study is a case study with descriptive data analysis using a qualitative approach. Based on the results of the study, it can be concluded that the level of member participation is not good because the retail strategy has not been maximized. Then, from the results of the SWOT analysis, it is known that the position of the Business is in quadrant I, namely supporting aggressive strategies. So the strategy that can be done is to utilize social media as a promotional tool in offering the products sold, increasing fixed suppliers by collaborating with other partners, offering pre-order products directly according to member requests, informing members of product discounts through social media, and maintaining credit purchases to trigger market expansion.